A sustainable design case: Re-examining traditional irrigation ollas as intangible cultural heritage - Akman, Zeynep Serra (ITU Graduate School, 2026)
Intangible cultural heritage (ICH) is recognized for supporting all three dimensions of sustainable development: environmental, social, and economic sustainability. In our age, however, many ICH elements are facing the risk of extinction due to the intensification of globalisation. Therefore, supporting any kind of ICH is a significant issue that requires human beings to take action. In the 2003 convention, UNESCO emphasized that safeguarding ICH elements should involve not only their protection and documentation, but also ensuring their continued vitality in contemporary contexts. In this view, implementing design can be a strategy for enabling the viability of ICH elements, as design can enable them to be incorporated into daily life and make them functional and meaningful for users. The study focused on the olla irrigation method as an ICH case that can provide up to 60% higher water efficiency compared to modern irrigation technologies. To explore the impact of design, a design-oriented qualitative research approach was adopted. To conduct a design-oriented qualitative research, olla irrigation was explored by investigating olla users' usage experience through a PD approach. Within the framework of the PD approach, a fieldwork was conducted through semi-structured interviews and structured forms to qualitatively explore the problems, needs and expectations of individuals who use the olla irrigation method. Semi-structured interviews were selected as the data collection method to gain an in-depth understanding of users' thoughts and experiences with the olla irrigation method. In addition, structured forms were adopted to support the semi-structured interviews and obtain further insights regarding user experience. The data obtained through interviews were analysed using thematic analysis. As a result of the thematic analysis, several themes were identified including: usage process, challenges and limitations, user motivations, personal meanings, and user suggestions and interventions. After the interviews, design implications were developed based on the data obtained through the interview process. The process of generating design implications proceeded in the following order: reading data, having insights, and generating design implications. Through the implications, the main focus areas of the design solutions were presented in four categories: usability, efficiency, user engagement, and customization. At the end, the actual meaning of such focus areas and their potential contributions to olla irrigation were discussed. These contributions were defined as satisfaction during use, outcome-oriented satisfaction, regular and continued use, and active adaptation and evolution.
Bir sürdürülebilir tasarım vakası: Geleneksel sulama testilerinin bir somut olmayan kültürel miras olarak yeniden incelenmesi
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2026
Keywords: sürdürülebilir tarım; sustainable agriculture; sürdürülebilirlik; sustainability; sürdürülebilir tasarım; sustainable design; sulama; irrigating; kültür varlıkları; cultural property